Drugs as Contemporary Global Threat (Related to issue of Collection of Reports by International Narcotics Control Board “Illegal Drug Trafficking: Tendencies and Problems”, compiled by Fedorov A.V.) - Yu. V. Golik (Московский журнал международного права)
At the end of 2007 there was issued Collection of Reports by International Narcotics Control Board (INCB), the task of which is to monitor the execution of treaties in the sphere of drug control. The Collection also includes INCB’s recommendations to the UN and other international and regional international organizations. Though it is necessary to mention that there were issued not reports themselves but introductory chapters to these reports.The wide variety of topics of the reports, which touches upon issues of legalization, globalization, etc. testify to the fact, that INCB’s approach to this problem is full-scale and its intentions are serious. It is very well noted that the tempo of life is accelerating and so the situation when the drug-related conventions were signed is rapidly changing. This poses a threat to the effective execution of treaties on the national level. The other major problem in drug control is the use of Internet in the promotion of drugs, as it poses no problem to find there the recipes of the simplest drugs. All these topics and many others are covered in the Collection.It is important to mention that the issue of this Collection of reports became possible due to the efforts and hard work of A.V. Fedorov, who is a well known scholar in the sphere of different aspects of crime control.